2020
DOI: 10.21203/rs.3.rs-32019/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of Low APGAR score in Newborns Delivered at Lemlem Karl General Hospital, Northern Ethiopia, 2018: A Case Control Study

Abstract: Abstract BACKGROUND: The Apgar score is a method to quickly summarize the health of newborn children. It establishes a simple and clear classification of newborns, which could be used to predict survival and to compare methods of resuscitation and perinatal experience across hospitals and obstetric practices. Low Apgar score is associated with various immediate and long-term adverse health outcomes of newborns. Hence; in order to decrease the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(28 reference statements)
3
1
0
Order By: Relevance
“…This study revealed that neonates born to mothers with PIH were 4.58 times more likely to have LAS than their counterparts [AOR = 4.58:95% CI (1.75-11.92)]. This is in line with studies done in Lemlem Karl general hospital, Northern Ethiopia [15], Sweden and India [24,25]. This might be due to, PIH causes placental ischemia.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study revealed that neonates born to mothers with PIH were 4.58 times more likely to have LAS than their counterparts [AOR = 4.58:95% CI (1.75-11.92)]. This is in line with studies done in Lemlem Karl general hospital, Northern Ethiopia [15], Sweden and India [24,25]. This might be due to, PIH causes placental ischemia.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the APH, newborns delivered from mothers with Antepartum hemorrhage were approximately four times (AOR = 3.96, 95% CI: 1.75 -8.94) more likely to develop low Apgar score compared to their counter parts. Moreover, the likelihood of encountering low Apgar score was 3.37 times (AOR = 3.37; 95% CI: 1.72 -6.62) higher among neonates born under general anesthesia compared to spinal anesthesia [15]. In this study, the higher odds of developing low Apgar score was also observed among neonates born by emergency CS compared to elective CS (AOR = 2.17;95% CI: 1.13 -4.15).…”
Section: Determinants Of Apgar Scoresupporting
confidence: 49%
“…16,30 Given APH increases the risk of compromised fetal blood perfusion, which leads to uteroplacental insufficiency, this might result in preterm birth and birth asphyxia and thereby NNM. 31,35 37 Similarly, neonates born to a mother with premature rupture of membrane (PROM) were more likely to have NNM, a finding supported by previous studies. 10,16,19 Since association of PROM with preterm birth, respiratory distress syndrome, intravascular hemorrhage, cord prolapse, reduced amniotic fluid volume, chorioamnionitis, neonatal sepsis, and birth asphyxia was reported, 38 40 this finding was expected.…”
Section: Discussionsupporting
confidence: 75%
“… 9 - 11 Premature rupture of membrane (PROM), prolonged labor, meconium stain-amniotic fluid, and fetal distress were intrapartum factors. 12 - 14 Low Apgar scores at the fifth minute are associated with mortality and may cause an increased risk of cerebral palsy. 5 , 15 , 16 Prolonged labor, low birth weight, pregnancy-induced hypertensive disorders, cesarean delivery, and meconium-stained liquor were identified determinants for low five-minute Apgar score.…”
Section: Introductionmentioning
confidence: 99%